STUDIES ON MOSQUITO REPELLENT ACTIVITY OF CYMBOPOGON CITRATUS (LEMON GRASS) USING HUMAN VOLUNTEERS - George, Iniodu; Edim, Hannah; Edet, Emmanuel (International journal of research - granthaalayah, 2016)
Background: Safety concerns over the use of chemical-based pesticides are provoking intense studies and application of bio-pesticides in disease control and agriculture. Aim: This qualitative study was aimed at testing the repellent efficacy; and suitability of Cymbopogoncitratus (Lemongrass) for the development of natural product-based mosquito repellent. Method: Cymbopogon oil (75ml) was extracted from 200g of fresh Lemongrass leaves using Soxhlet method with n-Hexane as solvent. Human volunteers were topically treated with 2ml and 6ml of Cymbopogon oil applied on exposed areas of the body at night; and observed for 4hrs 30mins. Direct test on mosquitoes in captivity was conducted using a 2-chambered insect box treated with 4 ml of oil in one chamber. Results: Human subjects were free from mosquito bites for 3 hours. Mosquitoes in captivity exhibited active movement away from oil-treated chamber of the box within the first minute of application; 43% repellency and 100% mortality were recorded after 18 minutes. Conclusion: Findings suggest that Cymbopogoncitratus extracts could be used for the production of potent chemical-free and safe mosquito repellent and insecticide for vector control in the fight against malaria and other mosquito-vectored diseases. However further studies and qualitative analyses are necessary to determine suitable concentrations for human topical application.